Telling Genes : The Story of Genetic Counseling in America - Stern, Alexandra Minna, 1966- (Book collections on Project MUSE., 2012)
For sixty years genetic counselors have served as the messengers of important information about the risks, realities, and perceptions of genetic conditions. More than 2,500 certified genetic counselors in the United States work in clinics, community and teaching hospitals, public health departments, private biotech companies, and universities. This work considers the purpose of genetic counseling for twenty-first century families and society and places the field into its historical context. Genetic counselors educate physicians, scientific researchers, and prospective parents about the role of genetics in inherited disease. They are responsible for reliably translating test results and technical data for a diverse clientele, using scientific acumen and human empathy to help people make informed decisions about genomic medicine. Here the author traces the development of genetic counseling from the eugenics movement of the early twentieth century to the current era of human genomics. Drawing from archival records, patient files, and oral histories, she presents the fascinating story of the growth of genetic counseling practices, principles, and professionals.